Microwave-assisted synthesis of europium(III) oxide decorated reduced graphene oxide nanocomposite for detection of chloramphenicol in food samples. (15th March 2019) - Rajaji, Umamaheswari; Manavalan, Shaktivel; Chen, Shen-Ming; Govindasamy, Mani; Chen, Tse-Wei; Maiyalagan, T.
Abstract: Herein, we describe an amperometric sensor for chloramphenicol (CAP) by using Eu2 O3 nanoparticles decorated reduced graphene oxide. A simple microwave-assisted synthetical route was employed to prepare Eu2 O3 NPs@RGO. it's structure and properties were characterized by x-ray diffraction pattern, Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, Field emission scanning electron microscope, High resolution transmission electron microscope. The electrical conductivity and cyclic voltammetry studies indicated the Eu2 O3 NPs@RGO modified electrode exhibited the best performance electrocatalytic sensing of CAP. An amperometric CAP sensor was found to be good sensitive and reproducible which able to detect concentration as low as 1.32 nM. The fabricated sensor worked well even applied in honey and fresh milk samples with appreciable recovery.